The Effect of ESG Performance on Audit Report Lag: The Moderating Role of Audit Firm Size - Askiantari, Anisa Eka; Rohman, Abdul (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on audit report lag (ARL) with audit firm size as a moderating variable. The study employs a quantitative approach using panel data from manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2024 period. Data were analyzed using panel regression with the Random Effect Model (REM). The results indicate that the governance score has a significant negative effect on audit report lag, while the environment score and social score do not show significant effects. Furthermore, audit firm size only moderates the relationship between social score and audit report lag, whereas no moderating effect is found for the environmental and governance dimensions. These findings suggest that auditors place greater emphasis on governance quality than on environmental and social disclosures in assessing audit risk and audit efficiency. This study contributes to the literature on ESG and audit timeliness in emerging markets and provides practical implications for companies, auditors, and regulators regarding the importance of governance quality and ESG integration in improving financial reporting timeliness.